2015
DOI: 10.3109/21678421.2015.1051988
|View full text |Cite
|
Sign up to set email alerts
|

A common functional allele of the Nogo receptor gene, reticulon 4 receptor (RTN4R), is associated with sporadic amyotrophic lateral sclerosis in a French population

Abstract: Amyotrophic lateral sclerosis is sporadic (SALS) in 90% of cases and has complex environmental and genetic influences. Nogo protein inhibits neurite outgrowth and is overexpressed in muscle in ALS. Our aims were to study the reticulon 4 receptor gene RTN4R which encodes Nogo 1 receptor (NgR1) in SALS, to test if the variants were associated with variable expression of the gene and whether NgR1 protein expression was modified in a transgenic mouse model of ALS. We genotyped three single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Only the rs1567871 SNP was included in both studies. In Amy et al’s ( 2015 ) study, the rs1567871 C allele was associated with SALS in the French population. However, the rs1567871 C allele was not a risk allele for SALS in the Chinese population.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Only the rs1567871 SNP was included in both studies. In Amy et al’s ( 2015 ) study, the rs1567871 C allele was associated with SALS in the French population. However, the rs1567871 C allele was not a risk allele for SALS in the Chinese population.…”
Section: Discussionmentioning
confidence: 91%
“…Four SNPs, rs854971, rs887765, rs696880 and rs1567871, were included in our study. Three SNPs, rs701427, rs701421 and rs1567871, were included in the French study (Amy et al, 2015 ). The MAFs of rs701427 and rs701421 were both lower than 0.2% in the Han Chinese population; therefore, these two SNPs were not included in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk allele C of rs854936 significantly raised the expression of RTN4R and high expression of RTN4R decreased the rate of HNC survival. RTN4R (reticulon 4 receptor), which is an essential role in axonal regeneration and structural plasticity in the central nervous system (19,20), has been elucidated to be associated with the risk for sporadic amyotrophic lateral sclerosis (21,22) and schizophrenia (23,24). That findings indicated that RTN4R might be a new risk factor for predicting cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of Nogo-A have been reported in schizophrenia (Novak et al, 2002), multiple sclerosis (Satoh et al, 2005), temporal lobe epilepsy (Bandtlow et al, 2004) and Alzheimer’s disease (Gil et al, 2006). An increasing number of mutations and genetic variants in genes depicted in Figure 1 have been found coupled to neuropsychiatric and neurodegenerative disorders, including schizophrenia (NgR1/Nogo-A: Budel et al, 2008; Willi and Schwab, 2013; Andrews and Fernandez-Enright, 2015), (LGI1/NgR1: Thomas et al, 2016), ALS (NgR1: Amy et al, 2015), Pelizaeus-Merzbacher disease (MAG: Lossos et al, 2015), Parkinson’s disease (Lingo-1: Chen et al, 2015), Tourette syndrome/OCD/ADHD (Olfactomedin: Bertelsen et al, 2015) and epilepsy (LgI1: Fukata et al, 2010); (ADAM22: Muona et al, 2016), further emphasizing the importance of normal Nogo-type control of synaptic plasticity. Current knowledge has also led to the initiations of clinical trials in spinal cord injury (NCT00406016), multiple sclerosis (Ineichen et al, 2017), and ALS in which disease a large phase II trial shows no positive effects of Nogo-A antibodies (Meininger et al, 2014).…”
Section: Discussionmentioning
confidence: 99%